2011
DOI: 10.2478/v10111-011-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vegetation change in marshy pine forest Vaccinio uliginosi-Pinetum Kleist 1929

Abstract: D³ugookresowe zmiany rooelinnooeci w zespole sosnowego boru bagiennego Vaccinio uliginosi-Pinetum Kleist 1929Long-term vegetation change in marshy pine forest Vaccinio uliginosi-Pinetum Kleist 1929 Abstract. Marshy pine forests have a relatively broad range of distribution across Europe but are very scattered. The typical Vaccinio uliginosi-Pinetum association is mainly restricted to nature reserves, because bog forests have been drained in many unmanaged sites where they naturally occur. Changes in the veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Long-term studies of autogenic successional changes in natural marshy pine forests (V. uliginosi-Pinetum) indicate a lowering of water tables and an increasing dryness of undisturbed peat bogs in Poland over the last 40 years (Czerepko, 2011). These results are in accord with the increase in potential evapotranspiration observed for Poland over the years 1970-2004 (Łabędzki et al, 2012).…”
Section: Leaching Of Metals Accumulated In Peatsupporting
confidence: 84%
“…Long-term studies of autogenic successional changes in natural marshy pine forests (V. uliginosi-Pinetum) indicate a lowering of water tables and an increasing dryness of undisturbed peat bogs in Poland over the last 40 years (Czerepko, 2011). These results are in accord with the increase in potential evapotranspiration observed for Poland over the years 1970-2004 (Łabędzki et al, 2012).…”
Section: Leaching Of Metals Accumulated In Peatsupporting
confidence: 84%
“…The BM raised bog seems to be more susceptible to adverse changes than JG. The only phytosociological record repeated after 25 years indicates that, besides an increase in the number of plant species in the northern part of BM, the tree cover there is now denser (CZEREPKO 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Land reclamation schemes, agriculture, afforestation and peat digging have fragmented them, thereby significantly reducing their coverage ( VAN SWAAY & WARREN 1999, VASANDER et al 2003. Simultaneous falls in the water table have made them susceptible to successional changes (CZEREPKO 2008(CZEREPKO , 2011. Peat bogs are characterized by a unique fauna and flora, and although there is little variety in the taxa recorded, they contribute significantly to global biodiversity (MINAYEVA 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the late-successional stages, the number of species typical to bogs was lower than in early-successional stages. Czerepko (2011) found that the share of species typical for bogs decreased and share of species typical for coniferous forests increased over the past 35 years in bog pine forests (Vaccinio uliginosi-Pinetum) of NE Poland. Based on data from the dendroecological and phytosociological inventories, this study showed differences in floristic composition of the plant associations studied.…”
Section: Differences In Floristic Composition Of Understory In Succesmentioning
confidence: 99%
“…This case study is different from the classical scheme of succession in raised bogs. This scheme includes massive entering of Scots pine and a stage of pine bog forest Vaccinio uliginosi-Pinetum, as an important phase of succession (Jasnowski 1962;Ellenberg 1988;Herbich 2001;Herbich and Herbichowa 2002;Herbichowa et al 2007;Czerepko 2010Czerepko , 2011. The lack of the Vaccinio uliginosi-Pinetum stage and even plant communities referring to this stage, both in this study as well as in historical materials (Maciantowicz et al 1999), suggests another course of succession.…”
Section: Model Of Succession In the Drained Transitional Bogmentioning
confidence: 99%